2018
DOI: 10.18203/2394-6040.ijcmph20181696
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and depression among caregivers of inpatients suffering from chronic debilitating and terminal illnesses

Abstract: Background: Depression and anxiety are the priority conditions covered by WHO’s Mental Health Gap Action Programme. Depression is a common illness worldwide, despite effective treatments available, fewer than half of those affected receive such treatments. Caregivers of the patients, attributed to bear higher burden of personal, financial, family, and social problems are expected to be predisposed to psychological illness. Thus this study was undertaken with following objectives; i) to estimate prevalence of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
0
0
Order By: Relevance
“…A study in Australia remarked that caregiving noticeable affected the lives and choices of caregivers such that they could not able to enjoy their holidays and travels, they do not have time to do their hobbies and socializing and resulted in social isolation and feeling of loneliness, grief and loss (36). An observational study of caregivers in India found out that all most all of them had some degree of anxiety and depression and 50% of participants in his study had severe level of anxiety and 63% had moderate to severe depression (42).…”
Section: Psychological Health Of Caregiversmentioning
confidence: 99%
“…A study in Australia remarked that caregiving noticeable affected the lives and choices of caregivers such that they could not able to enjoy their holidays and travels, they do not have time to do their hobbies and socializing and resulted in social isolation and feeling of loneliness, grief and loss (36). An observational study of caregivers in India found out that all most all of them had some degree of anxiety and depression and 50% of participants in his study had severe level of anxiety and 63% had moderate to severe depression (42).…”
Section: Psychological Health Of Caregiversmentioning
confidence: 99%